PENDAFTARAN TANAH ADAT UNTUK MENDAPAT KEPASTIAN HUKUM DI KABUPATEN KEPAHIANG - Sugianto, Bambang (Jurnal Panorama Hukum, 2017)
The birth of the Basic Agrarian Law UU No.5 of 1960 and Government Regulation No. 24 of 1997 concerning land registration is an order of Article 33 Paragraph (3) the web of the Constitution of the Republic of Indonesia 1945 to realize legal unification on registration of customary land in order to guarantee Legal certainty, orderly use of land and administration of land systems. In the registration of land raises several problems and obstacles. The constraints of the community is the high cost of registration and the community does not understand the function of the certificate so that people are not interested in registering land rights. In the implementation of the registration of land prosedure was long ago so tibul customary law (custom) prevailing in society is strong enough to regulate land issues either in the form of buying and selling, grants and inheritance. While the constraints of the government (ATR / BPN) there is no written proof of land rights and limited costs and technical personnel in the measuring and mapping in the registration of land and lack of extension provided to the community by the ATR / BPN office is causing less understanding of Use of certificates. In order to transition the rights of good sale and purchase, grants and inheritance are still mostly done by the community in front of the village head and the proof of ownership of rights to be found in the community, namely the seal made by the village head and written evidence made in a kinship. Besides the evidence there is unwritten evidence of continuous cultivation, the planting of harsh vegetation and borders and marks given by the right holder. To overcome these problems, the effort made by the office of ATR / BPN is not to submit deadline for submission of rights registration contained in the letter of recognition of rights. For customary property rights with no written proof of conversion, expensive fees are granted by ease and relief in the payment system for registration of customary property rights.